Case report: Recurrence of primary hepatic neuroendocrine tumors after resection of liver segments IV in 8 years follow-up - Li, Chunli; Bian, Li; Fan, Guangtao; Huang, Yilong; Li, Jiang; He, Bo (Frontiers in Medicine, 2024)
Background Primary hepatic neuroendocrine tumors (PHNETs) are an utterly rare entity. The diagnosis of PHNETs could legitimize when an extrahepatic primary NET must always be excluded. PHNETs can achieve a high survival rate after complete surgical resection, however, most patients still have an 18% risk of recurrence within 5 years after surgery. In our case, the recurrence occurred 8 years after the first hepatectomy, which is relatively rare in the current literature. Therefore, rigorous postoperative follow-up is necessary for early detection and timely treatment of recurrent PHNETs. Case information We report a case of PHNET in a 24-year-old previously healthy female patient who relapsed 8 years after hepatectomy. This case focuses on the importance of diagnosis of primary and recurrent PHNETS in young patients, rare pathological types, and post-operative follow-up. Conclusion This case report detailed the rare pathological morphology and characteristic immunohistochemical markers in our case for PHNETS, which enhanced the new understanding of the diagnosis of this entity. In addition, we also highlighted the variable duration of recurrence after treatment of PHNETs. The 8-year recurrent period in our case suggests the importance of regular examination in patients with PHNETs by following the doctor’s instructions.